Correction: Synthesis of non-toxic, biocompatible, and colloidal stable silver nanoparticle using egg-white protein as capping and reducing agents for sustainable antibacterial application. Issue 70 (26th November 2020) - Thiyagarajan, Kalaiyarasan; Bharti, Vijay K.; Tyagi, Shruti; Tyagi, Pankaj K.; Ahuja, Anami; Kumar, Krishna; Raj, Tilak; Kumar, Bhuvnesh
Abstract : Correction for 'Synthesis of non-toxic, biocompatible, and colloidal stable silver nanoparticle using egg-white protein as capping and reducing agents for sustainable antibacterial application' by Kalaiyarasan Thiyagarajan et al., RSC Adv., 2018, 8, 23213–23229, DOI: ; 10.1039/C8RA03649G .